An evaluation on Sri Java Kenderaan Sdn Bhd cost and service structure / Ahmad Khalib Saliya Ibrahim - Ibrahim, Ahmad Khalib Saliya (1991)
As stated in the Commercial Vehicle Licensing Board Act (CVLB) 1987, public service vehicle are divided into the following classes : 1. Charter buses 2. Stage buses 3. School buses 4. Mini buses 5. Factory buses 6. Express buses 7. Excursion/Tour buses 8. Taxis 9. Hired cars However in this study, concentration will only be focused on the stage bus and charter bus service and their operational costs. Stage bus is defined in CVLB Act 1987 as a bus used for the carriage of passengers at separate fare which contain no fare stage of not more than 32 kilometers. Stage bus acts as a local distribution system and as such it must show its important position to areas where the demand for it is needed.